2021
DOI: 10.1002/er.7495
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pretreatment conditions on the catalytic behavior and structure of Fe‐Co‐Mn / MgO FTS nanocatalyst: Modeling and optimization using RSM

Abstract: A co-precipitation procedure was employed for the preparation of supported Fe-Co-Mn oxide nanocatalysts. The prepared samples were evaluated for the hydrogenation of carbon monoxide to produce light olefins. After determining the optimum reductant agent type the influence of the other pretreatment factors including both reduction temperature and time, and the optimum flow of reductant agent was studied using response surface methodology (RSM). The modeling process for the selected responses was performed follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…It has been found that RSM is the most beneficial and potent procedure for optimizing and modeling various processes 47,48 . In our reported works we have also used the RSM method for modeling and optimization of preparation and pretreatment variables for light olefin production 49,50 . The RSM method is also a practical way to detect the most impressive variables and communication between factors; in this way, suitable models for the selected responses are achieved by fitting the variables.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that RSM is the most beneficial and potent procedure for optimizing and modeling various processes 47,48 . In our reported works we have also used the RSM method for modeling and optimization of preparation and pretreatment variables for light olefin production 49,50 . The RSM method is also a practical way to detect the most impressive variables and communication between factors; in this way, suitable models for the selected responses are achieved by fitting the variables.…”
Section: Resultsmentioning
confidence: 99%
“…47,48 In our reported works we have also used the RSM method for modeling and optimization of preparation and pretreatment variables for light olefin production. 49,50 The RSM method is also a practical way to detect the most impressive variables and communication between factors; in this way, suitable models for the selected responses are achieved by fitting the variables. In the present work, we attempted to investigate the influence of operational factors using the RSM method.…”
Section: Investigation Of Process Variable Via Rsmmentioning
confidence: 99%
“…By regulating the factors, the appropriate model is achieved from the favorable response. The RSM technique was also used in our previous works for CO hydrogenation reaction on the Fe–Co–Mn catalysts and Co–Ce bimetallic system 37–40 . In the current work, this technique (RSM) and the historical data design type of DOE are used in order to perform the optimization and modeling processes on the Fe–Mn/Al 2 O 3 nanocatalyst.…”
Section: Resultsmentioning
confidence: 99%
“…The RSM technique was also used in our previous works for CO hydrogenation reaction on the Fe-Co-Mn catalysts and Co-Ce bimetallic system. [37][38][39][40] In the current work, this technique (RSM) and the historical data design type of DOE are used in order to perform the optimization and modeling processes on the Fe-Mn/Al 2 O 3 nanocatalyst. Empirical data were fitted to polynomial equations by using the multiple regression analysis as follows:…”
Section: Influence Of Operational Conditions and Modelingmentioning
confidence: 99%